Dissolving the 'problem of the absent artifact': Design representations as means for counterfactual understanding and knowledge generalisation. (July 2015) - van Eck, Dingmar
Abstract : It has been argued by Per Galle that a viable account of designing should address the 'problem of the absent artifact'. The problem concerns the nature of design representations. Specifically, the question how one can utter true statements, in terms of design representations, about artifacts when these artifacts are, in the design phase, still non-existent. This paper exposes the problem as a pseudo-problem. It is argued that design representations are not means for the production of truth-apt assertions. This dissolves the 'absent artifact problem'. An alternative view is elaborated according to which design representations are means for counterfactual understanding, knowledge generalisation, and knowledge unification. Examples from the functional modelling literature are used to illustrate these roles. Highlights: The 'problem of the absent artifact' is a pseudo-problem. Norms pertaining to 'truth' conditions do not apply to the assessment of propositions based on design representations. Design representations are means for counterfactual understanding and knowledge generalization.